2017
DOI: 10.1136/bmjopen-2017-017178
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofLactobacillus rhamnosusGG andBifidobacterium lactisBb12 on beta-cell function in children with newly diagnosed type 1 diabetes: protocol of a randomised controlled trial

Abstract: IntroductionRecent evidence has demonstrated that, among other factors, dysbiosis (imbalances in the composition and function of the gut microbiota) may be relevant in the development of type 1 diabetes (T1D). Thus, gut microbiota may be a target for improving outcomes in subjects with T1D. The aim of the study is to examine the effects of Lactobacillus rhamnosus GG and Bifidobacterium lactis Bb12 on beta-cell function in children with newly diagnosed T1D.Methods and analysisA total of 96 children aged 8 to 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 34 publications
0
30
0
2
Order By: Relevance
“…Intestinal dysbiosis may influence the immune system by increasing gut permeability, intestinal inflammation, and impaired oral tolerance in T1D patients. Beneficial effect of Lactobacillus rhamnosus GG and Bifidobacterium lactis BB12 on β-cell function would create a rationale for its routine use in patients with newly diagnosed T1D [31]. Taken together, the studies imply that bacteriotherapy may potentially be used as a tool to modulate the immune system for preventing islet autoimmunity [31,32].…”
Section: Probiotic Applications In T1d Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intestinal dysbiosis may influence the immune system by increasing gut permeability, intestinal inflammation, and impaired oral tolerance in T1D patients. Beneficial effect of Lactobacillus rhamnosus GG and Bifidobacterium lactis BB12 on β-cell function would create a rationale for its routine use in patients with newly diagnosed T1D [31]. Taken together, the studies imply that bacteriotherapy may potentially be used as a tool to modulate the immune system for preventing islet autoimmunity [31,32].…”
Section: Probiotic Applications In T1d Patientsmentioning
confidence: 99%
“…The follow-up will be for 12 months. The primary outcome measures will be the area under the curve of the C-peptide levels during 2 h response to a mixed meal [31].…”
Section: Probiotic Applications In T1d Patientsmentioning
confidence: 99%
“…Probiotic treatment revealed promising effects for the control of T1D by improving overall islet function and gut‐islet immunomodulation . A multicenter prospective cohort study conducted by TEDDY in US and Europe from 2004 to 2014 on 8676 infants at risk of T1D revealed an association between exposure to probiotics and the incidence of islet autoimmunity .…”
Section: Modulation Of Gut Microbiome For Treatment Of T1dmentioning
confidence: 99%
“…120,121 Probiotic treatment revealed promising effects for the control of T1D by improving overall islet function and gutislet immunomodulation. 122 A multicenter prospective cohort study conducted by TEDDY in US and Europe from 2004 to 2014 on 8676 infants at risk of T1D revealed an association between exposure to probiotics and the incidence of islet autoimmunity. 123 The study concluded that supplementation of probiotics during the first 27 days of life is positively correlated with decreased islet-specific autoantibodies.…”
Section: Probiotics and Prebioticsmentioning
confidence: 99%
“…Type 1 diabetes mellitus (T1DM) is an autoimmune disease characterized by the progressive destruction of beta-pancreatic cells and the insufficiency of insulin production by these cells. 1 Genetic background and environmental factors are involved in the process of this disease. 2 The progression of disease is slow and may start before the diagnosis of T1DM.…”
Section: Introductionmentioning
confidence: 99%